Evidence of pockmarks and seafloor gas venting in the northwestern Arabian Sea - Ahmed Abdelmaksoud; Aisha H. Al-Suwaidi; Moamen Ali; Azeem Shah; Sara S. Almehairbi; Lamia M. Al Ali; Mohammed Y. Ali (Communications Earth & Environment)
Abstract Marine gas seeps are common along tectonically active margins, but they have not been previously observed along the Arabian continental margin. Here we present evidence of gas escape structures, pockmarks, and active gas seeps in the Gulf of Oman. Multibeam bathymetry, water column backscatter and physical parameters, and two-dimensional seismic reflection data were used to map active seafloor seeps and pockmarks. Circular and crescent-shaped pockmarks and complex pockmark strings were identified. These features are confined to regions shoreward of the shelf break. Thirty-five active gas bubble trains were observed, mostly not coincident with the mapped pockmarks. With progressive gas release, the gas seeps are anticipated to lead to development of pockmarks over time. Bright spots on the seismic data indicate shallow subsurface gas accumulation alongside normal fault and fracture conduits, strongly correlated to the presence of pockmarks. These findings suggest an important carbon flux into the Arabian Sea and atmosphere.